Degenerative joint disease in felines: case report and multimodal therapeutic approaches - Garcia, Larissa Costa (Pubvet, 2025)
Degenerative Joint Disease (DJD) is a progressive and often underdiagnosed condition in felines, primarily due to the subtlety of clinical signs and the species’ natural tendency to mask pain. This article aims to review the main aspects of DJD in cats, including its etiology, pathophysiology, clinical signs, diagnosis and treatment, as well as to present a case report of a young feline patient diagnosed with lumbosacral osteoarthritis. The clinical case reinforces the importance of behavioral assessment and the careful interpretation of subtle pain indicators, such as excessive licking and reluctance to jump. The multimodal therapeutic approach—consisting of anti-inflammatory drugs, analgesics, chondroprotective agents, and environmental modifications—resulted in a significant improvement to the patient’s quality of life. This study underscores the relevance of early detection of DJD, even in non-geriatric cats, and emphasizes the necessity for individualized and continuous strategies for managing chronic pain in felines.
Keywords: Chronic pain; cat; gabapentin; osteoarthritis